Association Between Depression and Peripheral Artery Disease: Insights From the Heart and Soul Study - Grenon, S Marlene (Blackwell Publishing Ltd, 2012)
BACKGROUND: Depression is known to increase the risk of coronary artery disease, but few studies have evaluated the association between depression and peripheral artery disease (PAD). We examined the association of depression with PAD and evaluated potential mediators of this association. METHODS AND RESULTS: We used data from the Heart and Soul Study, a prospective cohort of 1024 men and women with coronary artery disease recruited in 2000–2002 and followed for a mean of 7.2±2.6 years. Depressive symptoms were assessed with the validated 9-item Patient Health Questionnaire. Prevalent PAD at baseline was determined by self-report. Prospective PAD events were adjudicated on the basis of review of medical records. We used logistic regression and Cox proportional-hazards models to estimate the independent associations of depressive symptoms with prevalent PAD and subsequent PAD events. At baseline, 199 patients (19%) had depressive symptoms (Patient Health Questionnaire ≥10). Prevalent PAD was reported by 12% of patients with depression and 7% of those without depression (base model adjusted for age and sex: odds ratio 1.79, 95% confidence interval 1.06–3.04, P=0.03; full model adjusted for comorbidities, medications, PAD risk factors, inflammation, and health behaviors: odds ratio 1.59, 95% confidence interval 0.90–2.83, P=0.11). During follow-up, PAD events occurred in 7% of patients with depression and 5% of those without depression (base model adjusted for age and sex: hazard ratio 2.09, 95% confidence interval 1.09–4.00, P=0.03; full model adjusted for comorbidities, medications, PAD risk factors, inflammation, and health behaviors: hazard ratio 1.33, 95% confidence interval 0.65–2.71, P=0.44). Factors explaining >5% of the association between depression and incident PAD events included race/ethnicity, diabetes, congestive heart failure, high-density lipoprotein, triglyceride levels, serum creatinine, inflammation, smoking, and levels of physical activity. CONCLUSIONS: Depressive symptoms were associated with a greater risk of PAD. Because the association was explained partly by modifiable risk factors, our findings suggest that more aggressive treatment of these risk factors could reduce the excess risk of PAD associated with depression. (J Am Heart Assoc. 2012;1:e002667 doi: 10.1161/JAHA.112.002667.)